UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI PERUBAHAN SIFAT BENDA MENGGUNAKAN METODE INKUIRI - Ilmi Noor Rahmad; Mitra Budiyanti (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
Natural Sciences (IPA) is the result of human activities in the form of organized ideas and concepts, about the natural surroundings obtained from experience through scientific processes. In learning science, students must be active so that what is learned becomes meaningful. In the initial observation of science lessons at SDN Sukamaju 3, it was found that learning outcomes did not meet the predetermined KKM standard, namely 65, students who finished studying <30%, and student activities were less than optimal because the learning process was boring. This research is a classroom action research that aims to determine the improvement of science learning outcomes at SDN Sukamaju using the inquiry learning method. The subject of this research is the third-grade student number 23, this research is conducted in three cycles in each cycle an objective test is held. In the results of the research cycle I the percentage of student activity results is 69.56% and the average grade is 63.91, then in the second cycle the percentage of student activity is 78.26%, and the average value increases to 64.13, and in the third cycle the percentage student activity is 95.65%, and the average values reach 77.17. Based on the results of this study, it can be said that the application of the inquiry learning model in science lessons on the subject of changing objects can improve the learning outcomes of third-grade students at SDN Sukamaju 3, Tapos District, Depok City.